2022
DOI: 10.3390/cells11101705
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Signaling in Triple Negative Breast Cancer Cells Elicits the Annexin A1/Formyl Peptide Receptor 1 Axis and Affects the Tumor Microenvironment

Abstract: Annexin A1 (AnxA1) is a pleiotropic protein that exerts essential roles in breast cancer (BC) growth and aggressiveness. In our previous work, we described the autocrine signaling of AnxA1 through formyl peptide receptor 1 (FPR1) in the triple-negative (TN) BC cell line, MDA-MB-231. Here, we aimed to describe the interaction between the AnxA1/FPR1 and the Interleukin-6 (IL-6) signaling pathways and their role in the tumor microenvironment (TME). First, we demonstrated that AnxA1 and IL-6 expression levels are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…However, in addition to the well-documented role in immunity, there is significant evidence that ANXA1 is an important component of several upstream signalling pathways in a number of diseases [ 31 ]. In the context of cancer, ANXA1 has been shown to be involved in STAT3 [ 32 ], PI3K [ 33 ] and MAPK/ERK [ 11 ] signalling pathways which promote tumour initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the well-documented role in immunity, there is significant evidence that ANXA1 is an important component of several upstream signalling pathways in a number of diseases [ 31 ]. In the context of cancer, ANXA1 has been shown to be involved in STAT3 [ 32 ], PI3K [ 33 ] and MAPK/ERK [ 11 ] signalling pathways which promote tumour initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the well documented role in immunity, there is signi cant evidence that ANXA1 is an important component of several upstream signalling pathways in a number of diseases (33). In the context of cancer, ANXA1 has been shown to be involved in STAT3 (34), PI3K (35) and MAPK/ERK (11) signalling pathways which promote tumour initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 ] report that intact IL-6 signaling in T cells is important for controlling cancer progression and that IL-6 signaling in peripheral blood T cells at diagnosis is considered as a predictive biomarker for clinical result in BC. Vecchi et al [ 47 ] found that IL-6 expression was lower in BC samples classified as N1 and N2 and high in N0 samples.…”
Section: Discussionmentioning
confidence: 99%
“…Vecchi et al . [ 47 ] showed that IL-6 expression is elevated in triple-negative BC (TNBC), and weakly and moderately expressed in the other subtypes (luminal A, luminal B, and HER2+). Another in vitro study by Pe et al .…”
Section: Discussionmentioning
confidence: 99%